EXAMINING THE IMPACT OF AI TECHNOLOGY ON MARKETING STRATEGIES IN FINANCIAL SERVICES - POPESCU JENICA; SPULBAR LUCIAN FLORIN; SMARANDESCU ANDREI (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This article offers an examination of the transformative impact of artificial intelligence (AI) on marketing within the financial services sector, beginning with an exploration of the industry's evolution. As marketing strategies in financial services have shifted from traditional methods to digital-first, data-driven approaches, AI has emerged as a pivotal force driving efficiency, personalization, and customer engagement. The study delves into specific AI applications, such as predictive analytics for understanding customer behavior, machine learning models for dynamic customer segmentation, and automation tools that streamline targeted campaigns. Through a series of case studies, the article showcases real-world examples of AI-driven marketing successes in financial services, illustrating how companies are achieving enhanced customer satisfaction, increased operational efficiency, and data-driven decision-making. Despite these benefits, the discussion also highlights the potential drawbacks of AI adoption in this space, including ethical considerations, data privacy challenges, and the risk of over reliance on automated systems that could lead to diminished human oversight. By addressing both the powerful advantages and the inherent risks of AI in financial marketing, this article provides a balanced view of its role in shaping the future of customer engagement and operational excellence in financial services.